EVOLUTION AND CLASSIFICATION OF TRAGULINA (RUMINANTIA, ARTIODACTYLA) - Vislobokova L.A. (My University, 2001)
The main evolutionary trends of the Tragulina are traced and the systematics and phylogeny of this taxon are revised based on the study of the comparative morphology of fossil and Recent species and on the estimation of the polarity and taxonomic value of features. Nine families are included in the Tragulina. The existence of two main traguline groups is conﬁrmed, and the names Traguloidea and Hypertraguloidea are restored for these groups. The retention of many plesiomorphic characters shared with ancient eutherian mammals and the possession of very deep apomorphies distinguish tragulines from other artiodactyls and support a pre-Eocene origin of the Tragulina connected with the early radiation of artiodactyls.
Keywords: Tragulina; Eocene; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен